AKSIOLOGI ISLAM SEBAGAI FONDASI ETIS DALAM PENGEMBANGAN ILMU EKONOMI ISLAM - Mufidah, Farah Naila; Islam, Affan Riyazul; Rizky Ramadhani, Neng Gadis; Rocah, Muhammad Alpiah (Taksasila Edukasi Insani, 2025)
This study explores Islamic axiology as an ethical foundation in the development of Islamic economics, addressing the failures of conventional paradigms that neglect moral-spiritual values. Using a qualitative library research approach, this study analyzes the transformation of economic theory from a value-free to a value-bound paradigm. The findings indicate that Islamic economic axiology, rooted in Tawhid, reconstructs the human role from a mere homo economicus to a khalifah. Empirical evidence suggests that integrating ethics into financial instruments, such as the risk-sharing principle, provides superior systemic stability compared to debt-based systems. Furthermore, Islamic axiology serves as a crucial moral filter to mitigate exploitative risks in the era of digital disruption and artificial intelligence. The study concludes that Islamic economics aims not only for material profitability but also for the achievement of falah and maslahah as an embodiment of the Rahmatan lil ‘Alamin mission.Keywords : axiology, ethics, Islamic economics, maqasid al-shari’ah, maslahah.